Daily practices and territorialization processes: giving visibility to the informality experienced at traffic lights (Gestão & Regionalidade, 2023)
In this article, it was sought understand how daily practices occur in the process of territorialization of workers at traffic lights in the city of Maringá - PR. The theoretical contribution is supports on the concepts worked by De Certeau (2014), De Certeau, Giard and Mayol (2013) and Raffestin (1993). Therefore, through qualitative research, participant observation and thematic oral history interviews were carried out with workers between the months of May and September 2018. To interpret the data collected, the interviewees' narratives and the observations annotated in a field diary. The analysis allowed us to verify appropriation practices, resistance practices and small tricks. It was observed that time, age and hierarchy are fundamental in power relations and allow workers to territorialize space. Thus, in the midst of the uncertainties and prejudice they deal with daily, they resist, make bricolagens and build territorializations with the practice of informality.
Keywords: Daily; Territorialization; Informality; Street work; Traffic light